FRI0214 Clinical evaluation correlates poorly with ultrasound and magnetic resonance imaging of joints and entheses in early peripheral spondyloarthritis. (12th June 2018) - Renson, T.; Carron, P.; Krabbe, S.; Jans, L.; De Craemer, A.-S.; de Hooge, M.; Jacques, P.; Ostergaard, M.; Elewaut, D.; Van den Bosch, F.
Abstract : Background: Enthesitis is a hallmark of spondyloarthritis (SpA), which occurs in 30% to 50% of psoriatic arthritis patients (pts). 1 Evaluation of tenderness at the site of an enthesis with a standard palpation approach remains the gold standard for detection of enthesitis. However, inter- and intra-observer variability is rather high. All existing clinical enthesitis scoring systems lack validity. Imaging could avoid these drawbacks. Objectives: To compare the performance of ultrasound (US) and magnetic resonance imaging (MRI) with clinical examination (CE) of joints and entheses in peripheral (p)SpA. Methods: Clinical REmission in peripheral SPondyloArthritis (CRESPA) is a placebo-controlled trial of golimumab treatment in 60 early (symptom duration <12 weeks) pSpA pts. CE included tender and swollen joint count, dactylitis and enthesitis (evaluation of palpation tenderness) count. All pts underwent Power Doppler (PD)US of entheses and knee, talocrural (TC) and subtalar (ST) joints. Synovitis was scored according to the OMERACT-EULAR-US composite PDUS scale, giving a score of 0–3 for each joint. Entheseal sites were evaluated for hypoechogenicity and intraenthesis Doppler signal and were scored on a scale of 0–3. Modified whole-body MRI was performed at baseline. Bone marrow oedema (BME), synovitis and soft tissue inflammation (STI) were scored (scale 0–3) by 3 readers at several anatomical sites of pelvis and lower limbs. For each site a mean of the scores of the 3 readers was calculated. Results: Synovitis detected by US and MRI was most prevalent at knee joints (table 1). A discrepancy was noted between TC synovitis detected by CE, US and MRI. Enthesitis was most prevalent at Achilles tendon and plantar fascia. Regarding enthesitis, agreement between CE and US ranged from no (kappa −0.082) to moderate agreement (kappa 0.562). The highest agreement was observed at the entheseal sites of Achilles tendon (left 0.511, right 0.350) and plantar fascia (left 0.321, right 0.507). MRI did not correlate better with CE than US (kappa from −0.077 to 0.446). The correlation between MRI and US was overall poor and only in the Achilles tendon moderate (range −0.106 to 0.656). Conclusions: There was a weak agreement between CE and imaging in detecting enthesitis. In general, US detects less enthesitis compared to CE, while MRI detects more. Reference: [1] Gladmann DD, Chadran V. Observational cohort studies: Lessons learnt from the university of Toronto Psoriatic Arthritis Program. Rheumatology2011;50(1):25–31. Disclosure of Interest: None declared